Proprioceptive Neuromuscular Facilitation and/or Electrical Stimulation in Patients with Peripheral Facial Paralysis: A Systematic Review - Nerea Dominguez-Defez; Juan Lopez-Barreiro; Pablo Hernandez-Lucas; Ana González-Castro (Neurology International)
Background: Peripheral facial paralysis (PFP) affects the facial nerve, the seventh cranial nerve. It has an incidence rate of 20–30 cases per 100,000 habitants. The diagnosis is clinical, though imaging tests may be required in some cases. The treatment protocol includes medication, physiotherapy, and, in certain cases, surgery. Proprioceptive neuromuscular facilitation (PNF) techniques and electrical stimulation have been shown to be significant for recovery. Although PFP has a high recovery rate, up to 40% of patients may experience permanent sequelae. Objective: to assess the efficacy of treatment based on electrical stimulation and/or PNF in patients affected by PFP. Methods: A systematic search was conducted across six databases (PubMed, Medline, SportDiscus, CINAHL, Scopus, and Web of Science) in November 2024. Randomized controlled trials were included. Results: Fourteen articles were analyzed, applying PNF and/or electrical stimulation methods, pharmacological treatment, low-level laser treatment, subcutaneous collagen injections, and physiotherapy protocols involving facial expression exercises, yielding evidence for the variables assessed. Conclusions: PNF and/or electrical stimulation treatment in patients with PFP can be effective when employed early with appropriate parameters, showing promising results in improving quality of life, facial movement quality, and CMAP and reducing both the incidence and degree of synkinesis.